The Significance of the Hero’s Journey in Siddhartha’s Character Development as Seen in Herman Hesse’s Siddhartha - Adelia Damayanti; Achmad Munjid (Lexicon, 2020)
This paper discusses the character development of Siddhartha, the main character in Herman Hesse’s novel, Siddhartha (1973). This research aims to study how Siddhartha’s character develops during his journey to reach enlightenment. The analysis is conducted by using the theory of the hero's journey by Joseph Campbell. The result shows that Siddhartha’s journey follows twelve out of seventeen stages of the hero’s journey proposed by Campbell. All of the stages appear in the same order except the stage Belly of The Whale that comes late. It functions as a turning point rather than a preparation for a greater ordeal. The analysis also shows that Siddhartha undergoes two major changes; from an individualistic to a wise person and from someone who is always persistent and thirsty for knowledge to someone who is flexible.